Experimental Measurements of the {CO2 (1) + Acetone (2) + Ivermectin (3)} System at High Pressure - Junior, Osvaldo Valarini; Ferreira-Pinto, Leandro [UNESP]; Cabral, Vladimir Ferreira; Giufrida, Willyan Machado; Cardozo-Filho, Lúcio (American Chemical Society (ACS), 2019)
For potential application to the controlled release of ivermectin from nanoparticle preparations, this study discloses experimental data on the phase transitions in the CO2, acetone, and ivermectin system subjected to high pressures. The data were acquired via the static synthetic method with a variable-volume view cell in the temperature range of 303.15-333.15 K at pressures up to 10 MPa using three concentrations of ivermectin B1a in acetone (0.029, 0.043, and 0.058 mol·kg-1) and CO2 molar fractions of 0.3-0.9. Vapor-liquid-type phase transitions were observed, characterized as bubbles in the presence or absence of a solid phase. A solid phase was formed for all ivermectin B1a concentrations evaluated in this study. Determination of the region of precipitation of ivermectin is important for identifying the concentration of the acetone/ivermectin mixture where CO2 will act strongly as an antisolvent. Thermodynamic modeling was performed by considering the system as pseudo-ternary based on the low concentration of ivermectin B1a in the system. Thermodynamics modeling using the Peng-Robinson cubic state equation with the van der Waals mixing rule (PR-vdW2) adequately described the experimentally observed trends.